Design of multiple-frequency-band terahertz metamaterial absorbers with adjustable absorption peaks using toothed resonator. (January 2023) - Wang, Ben-Xin; Duan, Guiyuan; Xu, Chongyang; Jiang, Jieying; Xu, Wei; Pi, Fuwei
Graphical abstract: Highlights: A new strategy is presented to design multiple-band terahertz metamaterial absorber. Quad-band absorption is realized, the number of absorption peaks could be manipulated by reshaping resonator without increasing any design complexity. Introduction of temperature-controlled vanadium dioxide into the absorption system actively tunes the absorption peaks. This work opens a new space for the design and application of multiple-band metamaterial absorbers. Abstract: Multiple-frequency-band metamaterial absorbers possess great application prospects, which are usually achieved by vertically stacking or coplanar arranging several sub-resonators. Obtaining more absorption peaks requires further sacrifice of the number of sub-resonators. More importantly, these two design methods are difficult to control or adjust the number of absorption peaks without changing the number of sub-resonators. Therefore, new scheme using simplified structure without increasing any design complexity to realize multiple-frequency-band absorption with adjustable resonance features is urgently needed. In this paper, a multiple-frequency-band terahertz metamaterial absorber using surface structure of toothed resonator is demonstrated, it has the ability to control (increase or decrease) the number of absorption peaks without increasing its design complexity, which is different from previous works that need to sacrifice the design complexity of metamaterials. Furthermore, the introduction of temperature-controlled vanadium dioxide into the surface structure of multiple-frequency-band absorber can dynamically tune its resonance performance. It is proved that when vanadium dioxide changes from metallic state to insulating state, its absorption peaks can be actively adjusted from dual- to triple-, quad- and even penta-frequency-band absorption. These efforts could provide meaningful guidance for the design of multiple-frequency-band metamaterial absorbers, and could have broad application prospects in terahertz technology-related areas.